ChemInform Abstract: Hydrobromic Acid‐Catalyzed Friedel—Crafts Type Reactions of Naphthols. Issue 35 (2nd September 2014) - Xu, Cong; Yuan, Hongjuan; Liu, Yingjie; Wang, Mang; Liu, Qun
Abstract An unique catalytic activity of HBr in hydroxyalkylation and allylation—iodocyclization reactions of naphthols is established.